Modeling and simulation of water, heavy oil and air annular flow in horizontal ducts (Research, Society and Development, 2020)
This paper aims to study the three-phase flow of water - heavy oil - air in horizontal ducts, using the “core annular flow” technique. The non-homogeneous mathematical model in an Eulerian - Eulerian approach was used. The mixture model was considered to deal with the interfacial momentum transfer terms between the continuous phases (water and heavy oil) and the particle model to deal with the interfacial momentum transfer terms between the dispersed and continuous phases (air and heavy oil). All simulations were carried out using the CFX Software version 11. Results of the pressure fields and volume fraction of the phases and pressure drop in the duct are presented and compared with experimental data. It was found that the mathematical modeling used was adequate, presenting a maximum error in relation to the experimental data of pressure drop 7.3%, demonstrating the efficiency of the core-flow technique in predict transport of water - heavy oil – air in horizontal pipe.